Consequences of oxidative damage and mitochondrial dysfunction on the fatty acid profile of muscle of Indian Major Carps considering metal toxicity. (September 2018) - Das, Debjit; Das, Payel; Moniruzzaman, Mahammed; Poddar Sarkar, Mousumi; Mukherjee, Joyita; Chakraborty, Suman Bhusan
Abstract: Current study aims to find interrelation between mitochondrial enzyme function and fatty acid profile in fish muscle and role of antioxidant agents to maintain their balance in response to metal accumulation. Fishes ( Labeo rohita, Catla catla, Cirrhinus cirrhosus ) were collected from two sites (Nalban Bheri and Diamond Harbour, India). Concentrations of metals (lead, cadmium, copper, nickel, zinc), enzymatic and non-enzymatic antioxidant activity (malondialdehyde, superoxide dismutase, catalase, glutathione reductase, glutathione peroxidase, glutathione S-transferase), muscle enzyme activity (acetylcholinesterase, succinate dehydrogenase, lactate dehydrogenase, Ca 2+ ATPase, AMP-deaminase, lipoamide reductase, cytochrome C oxidase, aldolase) and fatty acid composition in muscle tissues were analyzed. Metal concentrations were significantly higher (P < 0.05) in fish muscles from Nalban compared to those in Diamond Harbour. Increased activity of antioxidant enzymes was noted with diminished mitochondrial enzymes activity and altered fatty acid composition in response to higher metal accumulation. Higher metal concentration in fish muscle of Nalban seems to significantly (P < 0.05) affect poly and monounsaturated fatty acid content, possibly due to oxidative damage and accumulation of hazardous reactive oxygen species (ROS) molecules. Changes in fatty acid contents following metal accumulation were observed to be species specific. Current study is the first correlative study to illuminate the level of oxidative damage and possible consequences on muscle cellular integrity, mitochondrial functionality and flesh quality against bioaccumulation of different metals in carps. Future studies are needed to quantify the relative contributions of enzymatic and low-molecular-mass antioxidants in protecting mitochondrial function and maintenance of proper fatty acid oxidation during acclimation to long term metal exposure. Graphical abstract: Image 1 Highlights: Metal pollution alters oxidative balance and affects mitochondrial enzymes activity. Metal exposure is likely to change the fatty acid composition of the carp muscle. Muscle mitochondrial enzymes regulate fish flesh quality against metal stress. Metal toxicity causes lipid peroxidation and subsequently alters carp muscle quality. Metal exposure alters PUFA, MUFA, omega fatty acid contents in carp muscle.